Visible-light induced photocatalyst-free difluoromethylation of quinoxalinones with difluorosulfones - Linlin Shi; Tiantian Li; Wenjing Zhang; Weinan Hu; Xinju Zhu; Yixin Lu; Guang-Jian Mei (Green Synthesis and Catalysis)
Visible-light induced direct C–H difluoromethylation of quinoxalinones with 2-((difluoromethyl)sulfonyl)benzo[d]thiazole has been developed for the first time. A broad range of quinoxalinones were well tolerated and reacted with difluorosulfone smoothly to give the corresponding products in moderate to good yields. Notably, no external photocatalyst or oxidant was required, which provides a practical and green protocol to access difluoromethylated quinoxalinones. Finally, the control experiments demonstrated a radical mechanism, and the density functional theory (DFT) calculations indicated the radicals were generated through the formation of an electron donor−acceptor (EDA) complex.